1997
DOI: 10.1038/sj.onc.1201472
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of a c-Myb/estrogen receptor fusion protein in transformed primary cells leads to granulocyte/macrophage differentiation and down regulation of c-kit but not c-myc or cdc2

Abstract: Primary murine fetal hemopoietic cells were transformed with a fusion protein consisting of the ligand-binding domain of the estrogen receptor and a carboxylterminally truncated c-Myb protein (ERMYB). The ERMYB-transformed hemopoietic cells exhibit an immature myeloid phenotype when grown in the presence of b-estradiol. Upon removal of b-estradiol, the ERMYB cells display increased adherence, decreased clonogenicity and di erentiate to cells exhibiting granulocyte or macrophage morphology. The expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
1

Year Published

2001
2001
2004
2004

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 43 publications
2
48
1
Order By: Relevance
“…Following terminal differentiation to monocytes, neutrophils, or erythrocytes, c-Myb is downregulated. 81,92 Genes implicated as targets of c-Myb which are involved in its role in proliferation include the cell cycle regulator gene Cdc2, 90 the DNA polymerase ␣ gene, 93 c-kit [94][95][96] and c-myc, [97][98][99] however recent studies question the regulation of c-myc by c-Myb. 89 In addition, antisense oligonucleotides to c-myb inhibit myeloid cell proliferation 100 and overexpression of c-Myb is known to inhibit cellular differentiation in erythroid and myeloid cell lines.…”
Section: C-mybmentioning
confidence: 99%
“…Following terminal differentiation to monocytes, neutrophils, or erythrocytes, c-Myb is downregulated. 81,92 Genes implicated as targets of c-Myb which are involved in its role in proliferation include the cell cycle regulator gene Cdc2, 90 the DNA polymerase ␣ gene, 93 c-kit [94][95][96] and c-myc, [97][98][99] however recent studies question the regulation of c-myc by c-Myb. 89 In addition, antisense oligonucleotides to c-myb inhibit myeloid cell proliferation 100 and overexpression of c-Myb is known to inhibit cellular differentiation in erythroid and myeloid cell lines.…”
Section: C-mybmentioning
confidence: 99%
“…A number of studies have demonstrated that c-Myb plays an important role in cellular proliferation and in the maintenance of cells in an immature, undifferentiated state (reviewed in Weston, 1998). Myb has also been shown to be involved in regulating apoptosis in some systems (Frampton et al, 1996;Taylor et al, 1996;Hogg et al, 1997). Overexpression of activated or normal forms of c-Myb has been shown to induce cellular transformation (Ferrao et al, 1995;Fu and Lipsick, 1997).…”
mentioning
confidence: 99%
“…In order to do this, we have utilized both cDNA array screening and PCR-based subtractive hybridization in conjunction with a conditionally Myb-transformed cell line, ERMYB (Hogg et al, 1997). This cell line was derived by transforming murine fetal liver cells with an activated form of Myb fused to the ligand-binding domain of the human estrogen receptor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(Methionine adenyl-transferase II, alpha) [236,243,244], Gata-3 [245], Rag-2 [168,169,246], c-kit [247][248][249], CD4 [245,250,251], and cyclin B1 [252]. However, many of these genes were identified by testing the ability of exogenously expressed c-Myb to activate promoter-reporter gene constructs in cells that do not normally express c-Myb [138,253] and it has recently been reported that the ability of Myb proteins to activate test constructs varied greatly from their ability to activate endogenous genes [154].…”
Section: Expression and Function Of Myb During Hematopoiesismentioning
confidence: 99%